2014
DOI: 10.1017/s0029665114000044
|View full text |Cite
|
Sign up to set email alerts
|

B-vitamins and bone in health and disease: the current evidence

Abstract: Osteoporosis, a metabolic skeletal disease characterised by decreased bone mass and increased fracture risk, is a growing public health problem. Among the various risk factors for osteoporosis, calcium and vitamin D have well-established protective roles, but it is likely that other nutritional factors are also implicated. This review will explore the emerging evidence supporting a role for certain B-vitamins, homocysteine and the 677C→T polymorphism in the gene encoding the folate-metabolising enzyme methylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 95 publications
1
34
0
Order By: Relevance
“…Zanchi et al demonstrated that children diagnosed with CD at a younger age showed the most robust BMD recovery versus older children and adolescents. 7 Even though vitamin deficiencies, presumably the result of malabsorption, are common in CD at diagnosis and may contribute to fracture risk 3, 38 , despite the initially depressed BMD 39 , following treatment with a GFD both adults and young patients with CD will show improvements in BMD. 12, 13 Risks of falls 40 and bone loss 41 increase with age, resulting in the overwhelming majority of osteoporotic fractures occurring in the elderly, particularly women.…”
Section: Discussionmentioning
confidence: 99%
“…Zanchi et al demonstrated that children diagnosed with CD at a younger age showed the most robust BMD recovery versus older children and adolescents. 7 Even though vitamin deficiencies, presumably the result of malabsorption, are common in CD at diagnosis and may contribute to fracture risk 3, 38 , despite the initially depressed BMD 39 , following treatment with a GFD both adults and young patients with CD will show improvements in BMD. 12, 13 Risks of falls 40 and bone loss 41 increase with age, resulting in the overwhelming majority of osteoporotic fractures occurring in the elderly, particularly women.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the maternal intake of folate and other methyl donors during pregnancy on DNA methylation patterns and offspring phenotype was established more than a decade ago using the agouti (A(vy)) mice which have a transposable element in the agouti gene (19) . Maternal supplementation with folic acid, vitamin B 12 , choline and betaine increased CpG methylation at the A(vy) locus in the offspring and increased the proportion of leaner offspring with darker coats (19) . The agouti locus is an example of a metastable epiallele (ME) that is variably expressed in genetically identical individuals due to epigenetic modifications that were established during early development (20) .…”
Section: Epigenetics As a Mechanism Linking Early Life Nutrition Withmentioning
confidence: 99%
“…Several cohort reports indicated that B-vitamins could play protective roles in bone health [56]. Homocystinuria is a rare autosomal recessive disease in which the metabolism of homocysteine is severely impaired, leading to excessive accumulation of homocysteine in the blood and urine (Fig.…”
Section: Snps In the Homocysteine And Folaterelated Genes And Fracturesmentioning
confidence: 99%